The Anti-inflammatory Effects of HMGB1 Blockades in a Mouse Model of Cutaneous Vasculitis - Wang, Jin; Fu, Lixin; Yang, Hao; Cao, Kai; Sun, Qiaomei; Chen, Tao (Frontiers in Immunology, 2020)
In our previous study, we have found increased serum levels of HMGB1 in patients with Henoch– Schonlein purpura (HSP), allergic vasculitis (AV), and urticarial vasculitis (UV) and altered HMGB1 distribution in lesional skin in patients with HSP. HMGB1 plays a pro-inflammatory role in the pathogenesis of HSP. To further investigate the role of HMGB1 in the pathogenic mechanism of vasculitis, we investigated the anti-inflammatory effects of HMGB1 blockades (including anti-HMGB1 mAb and glycyrrhizin) in a mouse model of a cutaneous reverse passive Arthus (RPA) reaction. A total of 36 balb/c mice were randomly divided into four groups: the control group, IC model group, HMGB1 monoclonal antibody (anti-HMGB1-mAb) group and the glycyrrhizin group, with nine mice in each group. A cutaneous RPA reaction mouse model was established by injections of the OVA antibody and the OVA antigen. Mice of the anti-HMGB1-mAb group and glycyrrhizin group were pre-treated with anti-HMGB1 mAb or glycyrrhizin, respectively, before the RPA reaction. Our results indicated that HMGB1 blockades (anti-HMGB1 mAb and glycyrrhizin) obviously extenuated the severity of vasculitis skin damage and improved the histological evolvement of inflammatory cells infiltration, vascular fibroid necrosis, and vasodilation in a cutaneous RPA reaction mouse model. In addition, HMGB1 blockades reduced the infiltration of neutrophils, DCs, and T cells and decreased the mRNA expression of IL-6 and CCL5 in skin lesions in the cutaneous RPA reaction mouse model. We suggest that HMGB1 blockades may represent a new direction for the treatment of cutaneous vasculitis.